The Private Sector and the SDGs: The Need to Move Beyond 'Business as Usual'. (30th March 2016) - Scheyvens, Regina; Banks, Glenn; Hughes, Emma
Abstract: In September 2015, world leaders gathered in New York to endorse the Sustainable Development Goals (SDGs): Ban Ki‐moon asserts that the SDGs signal a 'paradigm shift for people and the planet' (UN2014 : para. 24). Significantly, under this new agenda there are expectations that businesses, government and civil society actors will be equally responsible for progressing a more sustainable path forward. Many assert that the private sector has particular strengths to bring to bear in delivering on the SDGs, including innovation, responsiveness, efficiency and provision of specific skills and resources. Interestingly, the business sector had a strong role in influencing development of the SDGs. In this paper we discuss the challenge being put forth to business actors by the SDGs, reflecting on both the potential for more sustainable and responsible practices and on the limits to change. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment